Legal regulations regarding transplantation – in Poland, Germany and Switzerland - Huzarska, Dorota; Huzarska, Joanna; Pędziński, Bartosz; Sowa, Paweł; Szpak, Andrzej (Polish Journal of Public Health, 2015)
Introduction. Transplantation surgery, involving transplantation of cells, tissues and organs, constitutes a common medical practice that saves the lives of a great number of patients.Aim. The purpose of the present paper is to provide a comparative analysis of the legal regulations regarding transplantation that are in practice inside three European countries: Poland and Germany – EU Member States - and Switzerland – a non-EU state. The considerations made herein are meant to find an answer to the question whether the provisions of law regarding transplantation in the specified European countries regulate the legal situation of the donor and the recipient in a similar manner.Material and methods. The paper is based on the following source documents: The Cell, Tissue and Organ Recovery, Storage and Transplantation Act of July 1, 2005; The Act on Donation, Recovery and Transplantation of Organs and Tissues of November 5, 1997 (Transplantation Act – TPG); Federal Act on Transplantation of Organs, Tissues and Cells of October 8, 2004. In our work, we applied two methods, the first being comparative, and the second being dogmatic-legal. The latter consists of analyzing the provisions regarding transplantation as found within the three selected European countries.Results and Discussion. Under Polish, German and Swiss law alike, the recovery of cells, tissues and organs is allowed from an adult, who, under the Polish and German Acts, has full capacity to enter into legal transactions, and who, under the Swiss Act – is an adult who is mentally competent. Of note is that a minor might only be a donor in ex vivo transplantation provided that precisely specified requirements are met. Of additional note is that, under the German and Swiss Acts, recovery of tissues and organs from a human cadaver donor is allowed only if this person gave consent for such recovery prior to their death; under the Polish Act, this is allowed unless the deceased person expressed their objection when alive.Conclusion. As far as ex vivo transplantation is concerned, the legal solutions regarding transplantation in Poland, Germany and Switzerland regulate the legal situation of the donor and the recipient of a transplant in a similar way, although there are a few significant differences. As for ex mortuo transplantations – the legal solutions applied in each country greatly differ.